Parking Tax Management Evaluation in DKI Jakarta Province during 2022–2024 - Islamiyah, Erniati Rizki; Setyowati, Milla Sepliana (SAINTIS Publishing, 2025)
DKI Jakarta, as a national economic center, has potential off-street parking markings. Still, in managing parking taxes with an online system, the output is less than optimal in achieving the objectives of implementing parking tax policies. This study aims to evaluate the implementation of parking tax management in DKI Jakarta in 2022-2024. The method used is descriptive analysis with a post-positivist paradigm based on secondary data. The results of the study show that the realization of parking tax revenues against the set target has a very effective ratio, but the role of parking taxes is very poor in contributing to regional taxes, which indicates that the implementation of parking tax collection with an online system is less efficient. The output achieved has an increasing potential loss seen in 2024 higher than in 2023. The implementation of the parking tax policy applied through an online system is recommended to be evaluated by the DKI Jakarta Provincial Revenue Agency regarding the examination of parking tax objects and tax collection from tax payers that are less than optimal.